Double-gate (DG) MOSFETs: A review - Tiwari P.K.; Dubey S.; Jit S. (My University, 2025)
A detailed review of the double-gate (DG) MOSFETs has been presented in this chapter. Various configurations of the device structure have been discussed. A detailed review of the modeling and simulation of subthreshold characteristics in terms of threshold voltage, subthreshold swing and subthreshold current of the short-channel DG MOS devices has also been discussed. Finally, a doping dependent model for the subthreshold characteristics of a symmetric uniformly doped short-channel DG MOSFET has been presented in this chapter. © 2012 Nova Science Publishers, Inc. All rights reserved.